GIRK1 immunoreactivity is present predominantly in dendrites, dendritic spines, and somata in the CA1 region of the hippocampus - Drake, Carrie T. (The National Academy of Sciences of the USA, 1997)
Electron microscopic analysis of the CA1 region of the rat hippocampus revealed that specific immunoreactivity (IR) for a G protein-gated, inwardly rectifying potassium channel (GIRK1) was present exclusively in neurons and predominantly located in spiny dendrites of pyramidal cells. Within stratum lacunosum-moleculare and the superficial stratum radiatum, GIRK1-IR was often present immediately adjacent to asymmetric (excitatory-type) postsynaptic densities in dendritic spines. The subcellular localization of GIRK1-IR in the Golgi apparatus of pyramidal cell somata and in the plasma membrane of dendrites and dendritic spines confirms the hypothesis that GIRK1 is synthesized by pyramidal cells and transported to the more distal dendritic processes. G protein-coupled receptor activation of a dendritic potassium conductance would attenuate the propagation of excitatory synaptic inputs and thereby produce postsynaptic inhibition. Thus, these results show that the GIRK family of channels joins the list of voltage-sensitive channels now known to be expressed in dendritic spines.